Minced Cartilage in Combination with Autologous Bone Grafting for One-Step Osteochondral Defect Reconstruction in an Athlete’s Knee - Diane Leyder; Christian Konrads; Patrick Ziegler; Stefan Döbele (Case Reports in Orthopedics)
A 17-year-old student athlete suffering from stress-related knee pain asked for help. MRI revealed an unstable osteochondral lesion. Because of time pressure due to the patient’s academic exams and his schedule as a basketball player, an autologous chondrocyte transplantation (ACT) as the standard surgical treatment plan was not accepted by the patient. This was mainly because of its two-step character three weeks in between surgeries. Therefore, a surgical one-step therapy option as alternative treatment to ACT was needed. The patient received simultaneous autologous cancellous bone grafting and minced cartilage procedure in a sandwich technique. After successful rehabilitation, the patient continued his studies of sports science and his active career as a basketball player successfully. Several different procedures are used for the treatment of cartilage defects. The following factors play a significant role: defect size, location, patient age, and sports ambitions. In the case described here, ACT would have been the conventional, but not the ideal option in the perspective of this individual patient because of the two-step surgery and the longer rehabilitation time. Therefore, the minced cartilage method presented a valid alternative, even though long-term data are still missing and prospective studies comparing this procedure with others are needed in the future.